2021
DOI: 10.1007/s00384-021-03939-1
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art colorectal disease: postoperative ileus

Abstract: Purpose Postoperative Ileus (POI) remains an important complication for patients after abdominal surgery with an incidence of 10–27% representing an everyday issue for abdominal surgeons. It accounts for patients’ discomfort, increased morbidity, prolonged hospital stays, and a high economic burden. This review outlines the current understanding of POI pathophysiology and focuses on preventive treatments that have proven to be effective or at least show promising effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…Postoperative management should be standardized in a fast-track regime, including multimodal opioid-sparing analgesia using μ-opioid-receptor antagonists, epidural catheters and transverse abdominis plane block, early mobilization and oral nutrition, and goal-directed fluid therapy. Addittionaly, minimally invasive surgical approaches are recommended [ 41 ]. Kono-S anastomosis should be preferred in patients with CD undergoing an ileocecal resection, as it results in a wide anastomosis with significantly reduced recurrence rates of CD although it represents a hand-sewn anastomosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative management should be standardized in a fast-track regime, including multimodal opioid-sparing analgesia using μ-opioid-receptor antagonists, epidural catheters and transverse abdominis plane block, early mobilization and oral nutrition, and goal-directed fluid therapy. Addittionaly, minimally invasive surgical approaches are recommended [ 41 ]. Kono-S anastomosis should be preferred in patients with CD undergoing an ileocecal resection, as it results in a wide anastomosis with significantly reduced recurrence rates of CD although it represents a hand-sewn anastomosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2008 Cochrane Review of drugs to treat POI, erythromycin (used to treat ileus in the US) was shown to be ineffective for the treatment of ileus and the effects were inconsistent or insufficient evidence was available to recommend any other drugs, including serotonin agonists (cisapride), dopamine antagonists (metoclopramide), beta-blockers (propranolol), vasopressin, or cholecystokinin-like drugs (cerulatide) [19]. In a more recent review by Sommer et al, the authors concluded that although preventative methods have advanced, there are no evidence-based effective treatments for ileus once it develops [20]. Furthermore, several drugs to treat ileus have significant deleterious side effects that limit their use [19].…”
Section: Introductionmentioning
confidence: 99%
“…Most current preventative strategies are non‐specific and act by reducing the post‐operative inflammatory response, limiting opiate use and avoiding fluid overload, 9,11,12 yet despite these efforts, POI remains a common and troublesome issue following abdominal surgery. While there are promising developments, existing research has been limited by inconsistent definitions and an incomplete understanding of underlying pathophysiology 11 . This review aims to highlight controversies in the definitions and mechanisms of ileus, and identify areas for further research.…”
Section: Introductionmentioning
confidence: 99%
“…While there are promising developments, existing research has been limited by inconsistent definitions and an incomplete understanding of underlying pathophysiology. 11 This review aims to highlight controversies in the definitions and mechanisms of ileus, and identify areas for further research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation